2022
DOI: 10.3389/fphar.2022.828473
|View full text |Cite
|
Sign up to set email alerts
|

Trilobatin, a Natural Food Additive, Exerts Anti-Type 2 Diabetes Effect Mediated by Nrf2/ARE and IRS-1/GLUT2 Signaling Pathways

Abstract: Oxidative stress and aberrant insulin signaling transduction play vital roles in type 2 diabetes mellitus (T2DM). Our previous research has demonstrated that trilobatin (TLB), derived from the leaves of Lithocarpus Polystachyus (Wall.), exhibits a potent antioxidative profile. In the current study, we investigated the anti-T2DM effect of TLB on KK-Ay diabetic mice and further explored the potential mechanisms. Our results showed that TLB significantly reduced the high fasting blood glucose level and insulin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…First, we observed the effect of TLB on EEIF in mice by performing a weight-bearing swimming test and rope-climbing endurance test, which are the measurement indicators that directly reflect the exercise ability and the anti-fatigue capacity of drugs (Jiao et al, 2021). As we expected, the results in the present study indicated that TLB at doses of 5 and 10 mg/kg significantly prolonged exhaustive swimming time and the ropeclimbing dwell time of mice, in keeping with our previous finding that TLB act as a food additive against diabetes at the doses of 10 mg/kg (Shi et al, 2022). In addition, the consumption of energy substances and the accumulation of metabolites occur during EEIF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, we observed the effect of TLB on EEIF in mice by performing a weight-bearing swimming test and rope-climbing endurance test, which are the measurement indicators that directly reflect the exercise ability and the anti-fatigue capacity of drugs (Jiao et al, 2021). As we expected, the results in the present study indicated that TLB at doses of 5 and 10 mg/kg significantly prolonged exhaustive swimming time and the ropeclimbing dwell time of mice, in keeping with our previous finding that TLB act as a food additive against diabetes at the doses of 10 mg/kg (Shi et al, 2022). In addition, the consumption of energy substances and the accumulation of metabolites occur during EEIF.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we also determined the role of ferroptosis in the Nrf2-mediated anti-oxidative stress effect of TLB on EEIF. Ferroptosis, which is different from other forms of cell death (Zhang et al, 2022a), is associated with MDA accumulation and iron-overloading, and is negatively controlled by GPx4 (Zhang et al, 2022b), which is also a target of Nrf2 and a primary depressor for ferroptosis through reducing MDA and ROS production (Dong et al, 2021;Shi et al, 2022). As we expected, our results showed that TLB significantly up-regulated GPx4 protein expression and decreased the iron overload after EEIF insult.…”
Section: Discussionsupporting
confidence: 68%
“…Only one study reported trilobatin attenuated oxidative stress through the activation of the Nrf-2/ARE signal pathway. 16 Other possible sources of oxidative stress include a faulty antioxidative system and mitochondrial dysfunction. Whether DST affects these modules needs more exploration.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…For the oral glucose tolerance test (OGTT), mice were performed by glucose gavage (2 g·kg −1 ) after starvation for 12 h, and blood glucose levels were collected by pricking the tail vein at 0, 15, 30, 45, 60, 90, and 120 min after administration [ 28 ]. For intraperitoneal insulin tolerance test (IPITT), six-hour fasted mice were injected intraperitoneally with insulin (0.75 U/kg), blood glucose levels were measured sequentially from the tail vein at 0, 15, 30, 45, 60, 90, and 120 min after injection, and the area under curve (AUC) was calculated from the data collected during the OGTT and IPITT experiments.…”
Section: Methodsmentioning
confidence: 99%